I IMPROVING THE STUDENTS’ SPEAKING SKILL BY IMPLEMENTATION TEAM-BASED LEARNING (TBL) (A COLLABORATIVE CLASSROOM ACTION RESEARCH AT SMA NEGERI 3 BIREUEN) - Melly, Meli Sartika (Journal of English Education and Social Science, 2023)
This study aims to see whether the grade XI students of SMA Negeri 3 Bireuen get high scores in improving their English speaking skills using the Team-Based Learning method compared to the average scores of students using conventional methods. Methodology of this research is used collaborative classroom action research (CCAR). The researcher tried to improve students' speaking skills through the Team-Based Learning (TBL) method in this research. The researcher would use quantitative data as data collection. The data was collected from test, questionares, and an observation checklist. Thus, from this study, the researcher drew the following conclusions: The application of the Team-Based Learning (TBL) learning method improved students speaking skills in pronunciation accuracy and vocabulary suitability and students confidenced in speaking to second class SMA Negeri 3 Bireuen this could be proven through the results of students speaking test scores, namely in the cycle 1 got the result 46.67 or “good” categorized while in cycle 2 it reaches 86.67 or “excellent” categorized. The Students responses to the use of Team-Based Learning learning methods get satisfactory results. It could be seen that most students had a good response and are happy in learning to use this method. This could be seen from the results of the questionnaires answered by the students and the results of 3.65 (Strongly Agree). Based on the findings, the researcher conclude that the use of Team-Based Learning Method (TBL) in improving the speaking skills of students in the second class SMA Negeri 3 Bireuen Experienced a significant increased.